Research of information protection possibility by built-in packages of data cryptosecurity for MS SQL Server and Oracle certificates - Kabak, L.; Bulanyi, O. P.; Molotkov, O. N.; Kuts, V. V. (Systems and Technologies, 2019)
At the present time Oracle and MS SQL Servers are used for datastorage in the information system of department of customs control organization and for processing of State Fiscal Service of Ukraine. Data cumulated during customs clearance which requires access from all users are spread among many databases located between various physical storages. Data is passed between servers using different types of computer networks. With development of ramified informational systems and networks become a topical issue of ensuring sustaina-bility, confidentiality and authenticity of data in customs departments of fiscal service of Ukraine, which are transmitted through open data line, through usage of modern cryptography methods. It's important to know that there are different methods that help to choose such set of security tools that will provide maximum data security. To protect data from unauthorized access are used modern data encryption algorithms. At the present time data is transmitted over the computer network without usage of any crypt protection system which may give attacker opportunity to capture data. DBMS Oracle and MS SQL Server have standard built-in crypto data protection packets. The purpose of this article is to consider merits and demerits of using these packages and analyze possibility of their using in customs departments of fiscal service of Ukraine. According to research tech-nique in this article following tasks were solved: analyzing of built-in crypto data protection packets, as in their cryptostability, speed and volume increase of transmitted data, developing of plug-in for speed test of existing methods for crypt protection, considering possibility of implementation built-in packets into infor-mational system of fiscal service of Ukraine. In this article, the speed of algo-rithms work was investigated and an estimation of the growth of server loading and loading on the computer network was made due to the increase of data vo-lumes being transmitted. In the article, the method for evaluating the work of em-bedded symmetric data encryption algorithms has been further developed.